240 Original Article Ultrasound Scoring System for Pre-Operative Anticipation of Difficult Laparoscopic Cholecystectomy - Tayyiba Akhter , Junaid Khan Lodhi, Asim Malik , Rana Shakil Ahmad (Journal of Rawalpindi Medical College, 2018)
Background: To develop sonographic scoring criteria which would help the surgeons to predict the need for open cholecystectomy in cases in which laparoscopic surgery may be difficult and or may have a greater chance of conversion into an open cholecystectomy. Methods: Ultrasound findings of 100 patients treated by laparoscopic cholecystectomy were analysed from January 2016 to March 2018. Four variables (time taken, duct or arterial injury, biliary leakage and conversion to open cholecystectomy) were reviewed to classify laparoscopic cholecystectomy as easy or difficult. The sonographic findings recorded were : gall bladder wall thickness, distended gall bladder , impacted stones, pericholecystic fluid, multiple stones, common bile duct diameter, and liver size. Six variables out of total seven were taken to be statistically significant and a score of 2 was given to them. The rest of the parameters if positive were given a score of 1 each, amounting to a total score of 11. Finally, a value of 5 was considered to be cut off value to predict easy and difficult LC. Results: Twenty two out of 24 patients with difficult laparoscopic cholecystectomy and 74 out of 76 patients with easy LC were predicted correctly on account of this scoring system. A total score of 5 or more had a sensitivity of 91.2% and specificity of 98.7% for accurately predicting difficult LC. Ultrasound parameters of Gall bladder wall thickness, GB distension, Stone impaction, number of stones, CBD dilatation and presence of pericholecystic oedema were calculated to be significant statistically. Conclusion: Prediction of converting a difficult LC to OC can be done effectively by using an ultrasound score. Patients with higher score must be told preoperatively taking informed consent in written, scheduled suitably and anticipated early for conversion to OC.